Upaya Meningkatkan Hasil Belajar PKn Materi Norma Melalui Metode Pembelajaran Inkuiri Pada Siswa Kelas VIIID Di UPTD SMP Negeri 05 Bangkalan - Moh. Ali; Soubar Isman; Ernawati (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
This type of research used in this study is the type of Classroom Action Research (CAR). This research was conducted in 2 cycles, each cycle consisting of 1 meeting. Each cycle consists of four sides, namely planning, acting, observing and reflecting. Data collection techniques using tests and observations. The results of this study indicate how an increase in teacher skills, student activities and student learning outcomes in learning civics norm material through Inquiry learning methods in class VIIID students at UPTD SMP Negeri 5 Bangkalan. In cycle I, the average teacher skills gained 3.11 (good), the second cycle increased to 3.22 (good). In cycle I the average activity of students was 18.1 (enough), cycle II increased to 28 (good). Based on the value of learning outcomes obtained in the first cycle the average value obtained by students is 61.07. In cycle II the average value achieved by students becomes 75.09. Thus it can be concluded that by learning inquiry in Civics learning can improve teacher skills, student activities, and learning outcomes in class VIIID students of SMP Negeri 5 Bangkalan. The Inquiry Method improves the quality of learning so that it can be applied to other lessons.